(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article presents the methods and results of theoretical studies of photovoltaic energy converters using mathematical modeling of physical processes occurring in their volume at moments of non-stationary illumination. The dynamics of the free electron collection coefficient, voltage changes and photocurrent values under the influence of impulsive illumination due to pulsed illumination are shown. The main parameters for modeling work are indicated, and the simulation shows the time variation of the collection coefficient Q(t) and voltage u(t) for different absorption coefficients and light intensities. The studies used Fock’s law and Einstein’s relations, Green’s and Gauss function.